An empirical survey of the perceived benefits of executing BIM and sustainability practices in the built environment. Issue 3 (7th July 2019) - Olawumi, Timothy Oluwatosin; Chan, Daniel W.M.
Abstract : Purpose: The increasing urbanization of the built environment has bolstered the need to promote green Building Information Modeling (BIM) initiative in new construction projects and the rehabilitation of old premises. This study aims to explore and examine the key benefits of the implementation of BIM and sustainability practices in the built environment. Design/methodology/approach: The study gathered the worldwide perceptions of 220 survey participants from 21 countries which were analyzed using descriptive and inferential analytical methods. The identified individual benefits of green BIM were further categorized into their underlying clusters using factor analysis. Findings: The key benefits are related to enhancing project efficiency and productivity, ensuring real-time sustainable design and multi-design alternatives, facilitating the selection of sustainable materials and components, together with reducing material wastage and project's environmental impact, among others. The study analyzed and compared the perceptions of the diverse groups of the respondents as well. Practical implications: Effective blueprints and insightful recommendations for enhancing the various stakeholders' capacities to implement green BIM in their construction projects were put forward to achieve the aim of sustainable smart urbanization. Originality/value: The study identified salient benefits of the adoption of BIM and sustainability practices. The proper integration of these concepts and the execution of the recommended useful strategies by construction stakeholders, policymakers and local authorities will enable the built environment to reap the gains of its implementation.